2019
DOI: 10.3389/fpubh.2019.00057
|View full text |Cite
|
Sign up to set email alerts
|

Integrated Care for Latent Tuberculosis Infection (LTBI) at a Primary Health Care Facility for Refugees in Winnipeg, Canada: A Mixed-Methods Evaluation

Abstract: Although Canada has one of the lowest tuberculosis incidence rates in the world, certain groups are disproportionately affected, including foreign born people from high incidence countries. The Winnipeg Regional Health Authority has initiated a process to decentralize latent tuberculosis infection (LTBI) management at primary care clinics in Winnipeg. One of these clinics is BridgeCare Clinic which provides services to government-assisted refugees. The present study describes the BridgeCare Clinic LTBI program… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
47
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(50 citation statements)
references
References 19 publications
1
47
0
2
Order By: Relevance
“…The 39 included publications contained data on 31 598 migrants positive for LTBI. Studies were done in 13 countries, across three WHO regions (European region, region of the Americas, and Western Pacific region): Australia (n=4 studies), [31][32][33][34] Canada (n=3), [35][36][37] Germany (n=1), 38 Israel (n=1), 39 Japan (n=1), 40 the Netherlands (n=2), 41,42 Norway (n=2), 43,44 South Korea (n=1), 45 Spain (n=3), [46][47][48] Sweden (n=1), 49 Switzerland (n=1), 50 UK (n=4), [51][52][53][54] and USA (n=15). [55][56][57][58][59][60][61][62][63][64][65][66][67][68][69] In total, 25 studies with outcome data on 8764 migrants were used to calculate the proportion of individuals initiating treatment.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The 39 included publications contained data on 31 598 migrants positive for LTBI. Studies were done in 13 countries, across three WHO regions (European region, region of the Americas, and Western Pacific region): Australia (n=4 studies), [31][32][33][34] Canada (n=3), [35][36][37] Germany (n=1), 38 Israel (n=1), 39 Japan (n=1), 40 the Netherlands (n=2), 41,42 Norway (n=2), 43,44 South Korea (n=1), 45 Spain (n=3), [46][47][48] Sweden (n=1), 49 Switzerland (n=1), 50 UK (n=4), [51][52][53][54] and USA (n=15). [55][56][57][58][59][60][61][62][63][64][65][66][67][68][69] In total, 25 studies with outcome data on 8764 migrants were used to calculate the proportion of individuals initiating treatment.…”
Section: Resultsmentioning
confidence: 99%
“…[55][56][57][58][59][60][61][62][63][64][65][66][67][68][69] In total, 25 studies with outcome data on 8764 migrants were used to calculate the proportion of individuals initiating treatment. [33][34][35][36][37][38][39][41][42][43]48,[50][51][52][53][54][55][56][58][59][60]65,66,68,69 3A). Demographic and patient factors associated with noninitiation of treatment reported in the studies were being of sub-Saharan African origin 55 and being a refugee from sub-Saharan Africa, northern Africa, or the Middle East.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…LTBI treatment initiation and completion proportions were high, which is in contrast to a pilot study among immigrants [15]. Studies performed in other countries and settings also showed that these high proportions can be achieved among persons seeking asylum, provided that personalised LTBI treatment support by trained (TB) care staff, including education throughout the treatment process, is given [16][17][18][19]. Furthermore, the use of professional interpreters and peer educators is crucial to allow informed decision making of clients throughout the LTBI screening and treatment process, and these are important facilitators in LTBI treatment completion [20][21][22][23].…”
Section: Discussionmentioning
confidence: 57%